ENHANCING THE PRONUNCIATION OF ENGLISH SUPRASEGMENTAL FEATURES THROUGH REFLECTIVE LEARNING METHOD - Suwartono Suwartono (TEFLIN Journal: A publication on the teaching and learning of English, 2014)
Â Suprasegmental features are of paramount importance in spoken English. Yet, these pronunciation features are marginalised in EFL/ESL teaching-learning. This article reported a study that was aimed at improving the studentsâ mastery of English suprasegmental features through the use of reflective learning method. The study adopted Kemmis and McTaggartâs model of action research (1986) and involved twenty-four undergraduate students at Muhammadiyah University of Purwokerto, Indonesia as the subjects. The research consisted of two cycles, and data were gathered through observations, recorded conversations, diaries, interviews, and tests. Overall, the study has shown that reflective method using video integrated into communicative activities enhanced studentsâ pronunciation mastery. Interestingly, some studentsâ pronunciation to a great extent sounded âmore Englishâ.Â